2014
DOI: 10.1074/jbc.m114.602581
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Calpain Cleavage and Inactivation of the Sodium-Calcium Exchanger 1 in Heart Failure

Abstract: Background: Sodium-calcium exchanger 1 (NCX1) and calpain are up-regulated in heart failure (HF). Molecular mechanisms and functional consequences of NCX1 cleavage by calpain are not known. Results: Calpain anchors to two NCX1 regions and cleaves at methionine-369, leading to inactivation. Conclusion: NCX1 inhibition by calpain might improve cardiac function. Significance: Calpain might play a pivotal role in NCX1 regulation during HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 54 publications
1
26
0
1
Order By: Relevance
“…11A). We have previously shown that the NCX1 level is up-regulated in response to pressure overload in our animal model (15), similar to what others have shown (5,50). Anti-calsequestrin and anti-total PLM were used as controls.…”
Section: Pser-68-plm-ncx1-pp1c Complex Is Increased In Hf-mentioning
confidence: 95%
See 4 more Smart Citations
“…11A). We have previously shown that the NCX1 level is up-regulated in response to pressure overload in our animal model (15), similar to what others have shown (5,50). Anti-calsequestrin and anti-total PLM were used as controls.…”
Section: Pser-68-plm-ncx1-pp1c Complex Is Increased In Hf-mentioning
confidence: 95%
“…Staining without primary antibodies and use of an anti-NCX1 blocking peptide was used as a negative control. The proximity ligation assay was performed using the Duolink kit (DUO92014, Sigma) according to the manufacturer's protocol, as described previously (15). The cells were then incubated with 600 nM SYTOX Orange (S-11368, Life Technologies, Inc.), a nucleic acid stain, for 10 min at room temperature and rinsed three times for 5 min with PBS.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations